posted by carol .
In solving the equation (x + 4)(x – 7) = -18, Eric stated that the solution would be
x + 4 = -18 => x = -22
(x – 7) = -18 => x = -11
However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.
Eric does not understand the concept
It only works if the product is zero
so expand ....
x^2 - 3x - 28 = -18
x^2 - 3x - 10 = 0
(x-5)(x+2) = 0
x = 5 or x = -2